The Relationship Between Social Comparison with Social Anxiety in Youth Users Instagram in Jakarta - Mia Anita Lestari; Titin Aminatus Solekhah (Riviera Publishing, 2022)
Introduction: This study aims to see whether there is a relationship between social comparison and social anxiety in adolescent Instagram users in Jakarta. Method: The approach used in this research is quantitative. The measuring instrument used is an attitude scale that measures a social comparison scale and a social anxiety scale. The social comparison scale uses the Upward and Downward Psychological Appearance Comparison (UPADC) by Festinger (2011) and consists of 13 items, while the social anxiety scale is measured using the Social Anxiety Scale for Adolescents (SAS-A) proposed by La Gresa and Lopes (2005). and consists of 18 items. Subjects in this study amounted to 104 people who fit the research criteria. Results: The results obtained a correlation coefficient of 0.767 with a p_value of 0.000 (p<0.05). This result means that the null hypothesis is rejected and the alternative hypothesis is accepted by stating there is. Conclusion: Based on the results of this study, the researchers concluded that there was a significant relationship with a positive direction between social comparison and social anxiety in adolescents. Instagram users in Jakarta.